PENGARUH ATRIBUT PRODUK, HARGA DAN CITRA MEREK TERHADAP NIAT BELI MELALUI SIKAP PELANGGAN PENGGUNA SMARTPHONE SAMSUNG DI UNIVERSITAS STIKUBANK PERIODE TAHUN 2017 - Ega Tomy Andreawan, 12.05.51.0152; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2017)
The purpose of this study was to analyze the effect of variable product attributes, price, and brand image to re-purchase intentions through customer attitudes Samsung smartphone users. Respondents are students of the Faculty of Economics and Business who want and never buy a Samsung smarpthone as many as 140 people. The sampling technique used purposive sampling, and then analyzed using multiple linear regression. Data from the questionnaire were then tested by validity, reliability, hypothesis, and regression. Analysis using SPSS version 19.0. The result variable product attributes, price, and brand image influence on customer behavior and product attributes, price, brand image and customer attitudes influence on purchase intentions reset on Samsung smartphones. The final conclusion of this study can be recommended as an input for the management. Researchers believe that the approach through product attributes, price, brand image will affect the confidence and the evaluation of the customers attitude so as to create repeat purchase intention on Samsung smartphone products. This study has limitations of the sampling period is relatively short, and the population is limited to the scope of the Faculty of Economics and Business, University of Sikubank. Therefore, in future studies suggested considering the time in the sampling period and extend the range of the sample population data and information in order to obtain a more complete. Keywords: product attributes, price, brand image, customer attitudes and purchase intentions